O uso da linguagem simples para representar termos e definições nos produtos e serviços de informação jurídica: uma proposta baseada na abordagem design thinking - Keila Mara Lara Rosado (2024)
Legal language can (and should) be understandable to non-specialist citizens, as this enhances access to information and justice, making legal products and services more efficient, transparent, inclusive, and democratic. The research problem is translated into the following questions: how to use plain language to represent terms and definitions in legal products and services, ensuring semantic compatibility between the specialized language of law and non-specialist language? What benefits can this compatibility bring to citizens and the field of Knowledge Organization and Representation (KOR)? The general objective of the research is to propose an iterative and people-centered methodology to semantically harmonize specialized language with plain language, aiming to represent legal terms and definitions using the principles recommended by the international movements Plain Language, Legal Design, and Visual Law. It also aims to identify the benefits of this compatibility for citizens and KOR. Six specific objectives were established: 1) to survey the state of the art of projects, studies, or national and international standards related to language innovation and simplification movements, especially those initiated or applied in the field of Information Science or KOR, to understand and propose the research object; 2) to characterize Information Science and KOR, identifying their main processes, concepts, and tools to organize, represent, and retrieve knowledge that can contribute to harmonizing specialized language with non-specialist language in legal products and services; 3) to contextualize the fields of Linguistics, Terminology, information, documentation, and legal language, as well as the international innovation movements known as Plain Language, Legal Design, and Visual Law, and the Desing Thinking (DT) methodological approach; 4) identify the correlations and applications of these areas and theories in Information Science and KOR, especially the practices and principles that can be useful for conceptual modeling aimed at simplifying specialized language; 5) design an iterative, people-centered methodology that ensures semantic compatibility, with a view to representing terms and definitions in the legal field using plain, non-specialized language; 6) apply the proposed methodology to validate its practical feasibility, using terms and definitions from the Unified Tables of the National Council of Prosecution Services (UTNCPS) as an empirical study object. The research is characterized by a qualitative approach, with an applied purpose and a descriptive-exploratory method, utilizing the DT methodological approach. As a result, it presents a methodology proposal to harmonize specialized language with plain language, executing terminological work that involved long and meticulous cognitive effort, based on empathy and the principles of language simplification. The results also indicated that including terms and definitions with plain language in the structures of legal information products and services, such as the UTNCPS, can bring relevant contributions to KOR, reinforcing its mediating and social character, as it promotes the re-signification of these products and services for users, especially for those with lower levels of education and limited vocabulary.